ECG clues for false ST-segment elevation myocardial infarction activations. Issue 6 (September 2019) - Agrawal, Akanksha; Lu, Marvin; Kanjanahattakij, Napatt; Jeon, Hee Do; Romero-Corral, Abel; Figueredo, Vincent; Pressman, Gregg
Abstract : Background: Rapid diagnosis of ST-segment elevation myocardial infarction (STEMI) is crucial for appropriate management. Catheterization for a false STEMI activation has risks including exposure to contrast agent and radiation, increased healthcare costs and delay in treatment of the primary medical condition. Patients and methods: This was a single center retrospective study including all 'cath alerts' between January 2012 and December 2015. 'Cath alert' is a term used to activate the interventional cardiology team when STEMI is suspected by the emergency department physicians based on review of the initial ECG. We reviewed all STEMI alerts to understand ECG differences between true and false STEMI. Results: Our study population ( N = 361) included 221 (61%) men and 140 (39%) women, with average age 60 ± 4.2 years. Among the 361 STEMI alerts, 82 (22.7%) did not have acute coronary syndrome. Common ECG causes of misdiagnosis included left ventricular hypertrophy (LVH, found in 40/82, 49%), early repolarization changes (20/82, 24%), right bundle branch block (RBBB) (13/82, 16%), and Brugada pattern (3/82, 4%). Multivariate regression analysis showed that LVH and RBBB were independent predictors of nonacute coronary syndrome false STEMI (odds ratio: 0.54; 95% confidence interval: 0.32–0.93; P = 0.03 for LVH, and odds ratio: 0.26, 95% confidence interval: 0.1–0.62, P = 0.004 for RBBB). Conclusion: The incidence of false STEMI alerts was almost 23% at our center. This number might be reduced with additional training of emergency department physicians in ECG interpretation, and recognition of common causes of misdiagnosis such as LVH, early repolarization changes, RBBB, and Brugada pattern. Abstract : Rapid diagnosis of ST-segment elevation myocardial infarction (STEMI) is crucial for appropriate management. Catheterization for a false STEMI activation has risks including exposure to contrast agent and radiation, increased healthcare costs and delay in treatment of the primary medical condition. This was a single center retrospective study including all 'cath alerts' between January 2012 and December 2015. 'Cath alert' is a term used to activate the interventional cardiology team when STEMI is suspected by the emergency department physicians based on review of the initial ECG. We reviewed all STEMI alerts to understand ECG differences between true and false STEMI. Our study population (N=361) included 221 (61%) men and 140 (39%) women, with average age 60 ± 4.2 years. Among the 361 STEMI alerts, 82 (22.7%) did not have acute coronary syndrome. Common ECG causes of misdiagnosis included left ventricular hypertrophy (LVH, found in 40/82, 49%), early repolarization changes (20/82, 24%), right bundle branch block (RBBB) (13/82, 16%), and Brugada pattern (3/82, 4%). Multivariate regression analysis showed that LVH and RBBB were independent predictors of nonacute coronary syndrome false STEMI (odds ratio: 0.54; 95% confidence interval: 0.32–0.93; P=0.03 for LVH, and odds ratio: 0.26, 95% confidence interval: 0.1–0.62, P=0.004 for RBBB). The incidence of false STEMI alerts was almost 23% at our center. This number might be reduced with additional training of emergency department physicians in ECG interpretation, and recognition of common causes of misdiagnosis such as LVH, early repolarization changes, RBBB, and Brugada pattern.